2018
DOI: 10.1155/2018/9186237
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Traumatic Retinal Detachment: Clinical Features, Prognostic Factors, and Surgical Outcomes

Abstract: Purpose We report the clinical characteristics, prognostic factors, and surgical outcomes for 23-gauge pars plana vitrectomy (23-G PPV) in pediatric cases of traumatic retinal detachment (RD). Methods Medical records of pediatric patients who underwent 23-G PPV to treat traumatic retinal detachment were retrospectively reviewed. These patients underwent a follow-up examination at least 1 year following surgery. Associations between various preoperative factors and anatomical and visual outcomes were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
1
14
0
3
Order By: Relevance
“…Yasa et al concluded that OTS and POTS do not provide reliable prognostic information if the child has a detached retina. Even though the OTS and POTS include among their variables the presence or absence of a detached retina, their predictive value is low [38].…”
Section: Discussionmentioning
confidence: 99%
“…Yasa et al concluded that OTS and POTS do not provide reliable prognostic information if the child has a detached retina. Even though the OTS and POTS include among their variables the presence or absence of a detached retina, their predictive value is low [38].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the neuropsychiatric assessment was not conducted on patients with RD. Third, many predisposing factors of RD are common in the clinic; therefore, the VBM results of RD cannot be accurately evaluated (3–5).…”
Section: Discussionmentioning
confidence: 99%
“…Common risk factors for RD include high myopia, trauma, and cataract surgery, among others (3–5). Early symptoms of RD include acute-onset floaters and flashes of light, decreased central vision, visual distortion, and visual field defects (6).…”
Section: Introductionmentioning
confidence: 99%
“…Etiologi dari retinal detachment sesuai dengan subtipe dan trauma okuler merupakan etiologi paling umum pada pediatric retina detachment (Yaşa et al, 2018). Adapun manifestasi klinis dari retinal detachment seperti lapang pandang yang semakin menurun secara lambat dan progresif, floaters, fotopsia dan leukokoria (Kanukollu & Tripathy, 2021).…”
Section: Pendahuluanunclassified